2017
DOI: 10.1007/s00261-017-1084-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of CT urography in the evaluation of hematuria in young patients in a military population

Abstract: An unenhanced CT may be appropriate to evaluate new onset microscopic, and possibly gross hematuria, in patients younger than 40, even in patients at increased risk of urologic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similar results were demonstrated in a retrospective review of 137 patients younger than 50 years with hematuria and a history of military service, which increased their risk of urinary tract malignancy due to higher tobacco use and occupational exposures not seen in the civilian population 9 ; 63% of clinically significant findings, most commonly urolithiasis, were diagnosed on unenhanced CT images. Contrast-enhanced images were recommended in 10% of patients to confirm benignity of abnormalities detected on the unenhanced images.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were demonstrated in a retrospective review of 137 patients younger than 50 years with hematuria and a history of military service, which increased their risk of urinary tract malignancy due to higher tobacco use and occupational exposures not seen in the civilian population 9 ; 63% of clinically significant findings, most commonly urolithiasis, were diagnosed on unenhanced CT images. Contrast-enhanced images were recommended in 10% of patients to confirm benignity of abnormalities detected on the unenhanced images.…”
Section: Discussionsupporting
confidence: 74%
“…However, multiple studies demonstrating few clinically significant upper urinary tract findings in patients with hematuria, particularly in the younger population, suggest that indiscriminate exposure of patients to the high radiation doses of multiphasic CTU may not be indicated. [2][3][4][5][6][7][8][9] In patients with a bladder malignancy, the AUA recommends upper tract imaging for staging given the risk of a synchronous upper tract malignancy. 10 However, the benefit of upper tract imaging in patients evaluated for hematuria with negative cystoscopy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study comparing CTU with unenhanced CT in the evaluation of asymptomatic microscopic hematuria in 442 adults <50 years old identified no upper urinary tract malignancies and calculated a theoretical maximum risk of 0.7% to 1.1%. 20 Mace et al 21 also found no malignancies in 137 patients <50 years of age with hematuria who were at increased risk of urological cancer. These studies affirm that the detection rate of upper urinary tract malignancies with CTU is exceedingly low in certain subgroups of patients.…”
Section: Discussionmentioning
confidence: 95%